2011
DOI: 10.1007/s13369-011-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Response Surface Methodology to Optimize the Extraction of Silica and Alumina from Coal Fly Ash for the Synthesis of Zeolite Na-A

Abstract: Response surface methodology and inductively coupled plasma-optical emission spectroscopy were used to analyze the silicon (Si) and aluminum (Al) ion concentrations extracted from microwave-assisted hydrothermal fusion reactions between coal fly ash (CFA) and sodium hydroxide solution. The extracts containing Si and Al ions were successfully converted to zeolites by hydrothermal treatment at 95 • C for 72 h. Fifteen experimental conditions for the extraction process were obtained using Box-Behnken design throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In Table S1, the p-values for all the models were less than 0.05, which usually indicates that the models are significant, 2 meaning that the quadratic model of the CCD chosen was sufficient to represent silica extraction. This model is in agreement with what was found by Adebisi et al 13 , Olawale et al 22 , Matlob et al 23 and Qisti et al 24 However, p-values for many of the terms in the CSE and acid UAE methods were greater than 0.05. This value means that those terms are not significant model terms implying that they do not directly impact the percentage yield or the percentage purity of silica extracted.…”
Section: Rsm Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…In Table S1, the p-values for all the models were less than 0.05, which usually indicates that the models are significant, 2 meaning that the quadratic model of the CCD chosen was sufficient to represent silica extraction. This model is in agreement with what was found by Adebisi et al 13 , Olawale et al 22 , Matlob et al 23 and Qisti et al 24 However, p-values for many of the terms in the CSE and acid UAE methods were greater than 0.05. This value means that those terms are not significant model terms implying that they do not directly impact the percentage yield or the percentage purity of silica extracted.…”
Section: Rsm Modelsupporting
confidence: 92%
“…For example, all modelled factors directly impact the percentage yield and purity of silica extracted in the alkali UAE method since the change in Na + ions, time, and transient temperature will affect the amount of sodium silicates produced. A study by Matlob et al 23 also found that a change in NaOH concentration, exposure time and microwave power level significantly affected the concentration of Si in coal fly ash extracts. On the other hand, neither concentration of alkali nor stirring time nor the interaction as their crossed vector of both nor their quadratic functions had any effect on percentage yield in the CSE method.…”
Section: Rsm Modelmentioning
confidence: 94%
“…sialate ions. As the result of these reactions, stable material similar to zeolite is formed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A polysialatesiloxo (SiO2/Al2O3 =4) is obtained from metakaolin and NaOH. These inorganic polymers have a chemical composition somewhat similar to zeolite A [19,20], but exist as amorphous solids rather than having a crystalline microstructure [22,23].…”
Section: Introductionmentioning
confidence: 99%